4,4′-Diaponeurosporene-Producing Bacillus subtilis Increased Mouse Resistance against Salmonella typhimurium Infection in a CD36-Dependent Manner - Liu, Haofei; Xu, Wenwen; Yu, Qinghua; Yang, Qian (Frontiers in Immunology, 2017)
Deficient mucosal innate immunity is a hallmark of infectious diarrhea, such as Salmonella typhimurium (S. typhimurium) induced gastroenteritis. Here we report that orally administration of a 4,4’-diaponeurosporene-producing Bacillus subtilis (B.s-Dia) could improve mice mucosal immunity, as showed by an increased resistance against S. typhimurium infection. Intragastric administration of B.s-Dia for 7 days could increase the secretion of CCL20 by intestinal epithelial cells (IECs) and then recruit more dendritic cells (DCs). Meanwhile, the number of CD8αα+ intraepithelial lymphocytes (IELs), which play a critical role on down-regulating immune responses, was also reduced, probably as a consequence of the decrease of IECs derived TGFβ. Further study showed that CD36 played a critical role in B.s-Dia induced immune enhancement, as blocking CD36 signal with a specific antagonist, Sulfo-N-succinimidyl Oleate (SSO), leaded to the inability of B.s-Dia to enhance mucosal innate immunity.